Molecular modeling, structural analysis and identification of ligand binding sites of 1-deoxy-D-xylulose-5-phosphate reductoisomerase (DXR) of Theileria parva: a potential target for antitheilerial - Taskin, I. Icen; Munzuroglu, O. (Wiley-Blackwell, 2016)
[Abstract Not Available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY